Trapped by law - Mustafa, Sami; Romawood (Firm) ([Plemetina, Kosovo] : Romawood, 2015)
During a dramatic night in March 2010, two brothers, Kefaet and Selami, rappers from Essen, are deported to Kosovo, a complete unknown country to them. Separated from their family and friends they try to cope with their situation and do everything in their power to return to Germany. But administration and asylum laws are standing in their way.--
Originally released as a motion picture in 2015.
Kefaet Prizreni, Selami Prizreni, Sami Mustafa.
Cinematographers, Janis Mazuch, Faton Mustafa, Sami Mustafa ; editors, Carina Mergens, Nicole Kortlüke ; music, Luigi Montanino, Kefaet Prizreni, Selami Prizreni.
A mix of German, English, Romanian, Serbian, and Albanian with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed September 27, 2019)
Keywords: Romanies -- Kosovo (Republic); Rap musicians -- Kosovo (Republic); Deportees -- Kosovo (Republic); Documentary films; Nonfiction films; Internet videos; Streaming video